Oposisi Berseragam: Catatan Tentang Hubungan Politik Suharto dan Militer di Akhir 1980-an - Dwi Pratomo Yulianto (Jurnal Ilmu Sosial dan Ilmu Politik, 2003)
In playing its predominant role in Indonesia politics during the New Order era, the military, in fact, suffered from intergroup rivalry. The emerging ballance of power among the competing factions, on the one hand allowed Suharto to keep control the military and on the other hand complicates president's relation to the military. The order to win internal struggle for power within the military faction, one of them invite more political opennes and encourage a wider opposition. The competing faction eventually gained nothing.